Characterization of the hydantoin-hydrolysing system of Pseudomonas putida RU-KM3s - Matcher, Gwynneth Felicity (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2005)
The biocatalytic conversion of 5-monosubstituted hydantoin derivatives to optically pure amino acids involves two reaction steps: the hydrolysis of hydantoin to N-carbamylamino acid by an hydantoinase or dihydropyrimidinase enzyme, followed by conversion of the Ncarbamylamino acid to the corresponding amino acid by an N-carbamoylase enzyme. This biocatalytic process has been successfully applied in several industrial processes for the production of enantiomerically pure amino acids used in the synthesis of pharmaceuticals, insecticides, hormones, and food additives. P. putida RU-KM3S was selected for study based on inherent high levels of hydantoinase and N-carbamoylase activity. Subsequent biocatalytic analysis of the enzyme activity within this strain revealed unique properties thus prompting further characterization. The main focus of this research was the isolation of the genes encoding the hydantoin-hydrolysing pathway in RU-KM3S. A genomic library was constructed and screened for heterologous expression of the hydantoin-hydrolysing enzymes. However, this approach was unsuccessful prompting the use of transposon mutagenesis in order to circumvent the drawbacks associated with complementation studies. The enzymes responsible for hydantoin-hydrolysis were identified by insertional inactivation as a dihydropyrimidinase and b-ureidopropionase encoded by dhp and bup respectively. A third open reading frame, encoding a putative transport protein, was identified between the dhp and bup genes and appeared to share a promoter with bup. Analysis of the amino acid sequence deduced from bup and dhp substantiated the distinctive properties and potential industrial application of the L-enantioselective b-ureidopropionase and provided targets for potential optimisation of the substrate-selectivity and activity of the dihydropyrimidinase by site directed mutagenesis. Several transposon-generated mutants with an altered phenotype for growth on minimal medium with hydantoin as the sole source of nitrogen were also isolated. Analysis of the insertion events in these mutants revealed disruptions of genes encoding key elements of the Ntr global regulatory pathway. However, inactivation of these genes had no effect on the dihydropyrimidinase and b-ureidopropionase activity levels. An additional mutant in which the gene coding for the dihydrolipoamide succinyltransferase, which is involved in the TCA cycle, was isolated with reduced levels of both dihydropyrimidinase and b-ureidopropionase activities. These results indicated that the hydantoin-hydrolysis pathway in RU-KM3S is regulated by carbon rather than nitrogen catabolite repression. This was confirmed by the reduction of hydantoin-hydrolysis in cells grown in excess carbon as opposed to nitrogen. Identification of a putative CRP-binding site within the promoter region of these enzymes further supported the regulatory role of carbon catabolite repression (CCR). As CCR in Pseudomonads is poorly understood, elucidation of the mechanism by which the hydantoinhydrolysing pathway in RU-KM3S is regulated would provide valuable insight into this complex process.
Keywords: Hydantoin; Hydrolysis; Pseudomonas; Enzymes